2019
DOI: 10.22435/jhecds.v4i2.218
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran status gizi dan faktor risiko kecacingan pada anak cacingan di masyarakat Dayak Meratus, Kecamatan Loksado, Kabupaten Hulu Sungai Selatan

Abstract: Helminthiasis is a disease caused by intestinal parasite helminth with a high prevalence and spread throughout Indonesia, not deadly but secretly and slowly affect the health and productivity of patients through the decline in nutritional status. Slow and less symptom-prone effects cause the disease to be neglected among other diseases. This research is descriptive observational with cross sectional design, to know the description of nutritional status and risk factors of helminthiasis at elementary school chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
8
0
4
Order By: Relevance
“…Students of 5 th grade had the highest proportion of STH infections (55.56%). 11,12 The results of this study indicate that the prevalence of STH infections is 10.84% with the highest proportion is a Trichuris trichiura. This result is accordingly but lower than the study conducted by Sofiana et al who also found Trichuris trichiura as the major type of STH infection with a proportion of 24.6%.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Students of 5 th grade had the highest proportion of STH infections (55.56%). 11,12 The results of this study indicate that the prevalence of STH infections is 10.84% with the highest proportion is a Trichuris trichiura. This result is accordingly but lower than the study conducted by Sofiana et al who also found Trichuris trichiura as the major type of STH infection with a proportion of 24.6%.…”
Section: Resultsmentioning
confidence: 72%
“…1 Annida et al reported the majority of children in Dayak Meratus community (80.4%) had the habit of playing in the yard and used soil as the game media were associated with hookworm infections. 11 Samad's research also found that 52.5% of the soil contaminated with Ascaris lumbricoides eggs in Tembung, Medan was associated with the incidence of STH infections among elementary school students. 14 The STH transmission is easier found among the children who often play or have contact with the ground.…”
Section: Resultsmentioning
confidence: 93%
“…Another symptom of worms is lowering the appetite so that the weight will continue to decrease. Worms are an emergency disease often overlooked because they appear without clinical symptoms (Annida, Fakhrizal, Juhairiyah, & Hairani, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Cacingan merupakan penyakit di daerah tropis yang bisa ditularkan melalui tanah dan menyebabkan infeksi di rongga usus yang dapat mengakibatkan kehilangan karbohidrat, protein, dan kehilangan darah dan disebabkan karena kurangnya kebersihan diri dan sanitasi yang buruk (Rahman., 2017). Menurut Annida (2018) bahwa penyakit kecacingan memang bukan menjadi penyakit yang mematikan namun jika anak-anak menderita kecacingan akan dapat berdampak terhadap kejadian infeksi yang meningkat dan mengalami penurunan status gizi.…”
Section: Pendahuluanunclassified